Theoretical model for strategic alignment in organizations, a hidden value in education - Salgado García, Lorenzo (2019)
The issue of strategic alignment is an added value to the content presented, as you can see, how the strategic approach goes beyond planning and penetrates all management functions, demanding an integrated look at the whole process of address. It is of great interest how the issue of alignment to the use of models of excellence and continuous improvement, so that the quality of education is a substantial element of the strategy is also integrated. The significant interest that exists for capacity alignment, as an element of organizational culture and dynamic absorption capacities, as an element triggering the dynamic capabilities of coordination, as necessary to achieve a culture of alignment in organizations. Therefore, it prints a special value contextualize the topic because the theoretical result is adapted to the conditions of economic and educational organizations, providing answer to the basic question of this work, namely: What is the hidden value of the Mexican organizations ? Which is an additional value that has provided the alignment between the efforts of the cooperated work. Therefore, the article will fill an important gap in the scientific and academic literature devoted to the study of the strategic approach in the management of organizations of Mexico. Thus, the coordination process in which alignment factors are identified and organizational conditions are created so that becomes effective cooperation and integration between the resources, capabilities, and processes involved in the implementation of the strategy demands the manifestation of these factors.